CHLORPYRIFOS DEGRADATION IN SOIL AND ITS EFFECT ON SOIL MICROORGANISMS - S. T. S. Gilani; M. Ageen; H. Shah; S. Raza (Journal of Animal and Plant Sciences, 2010)
This study was designed to determine the degradation of chlorpyrifos, an organophosphate (OP) insecticide used now a day for termite control in replacement of heptachlor. Beside this it is also used on agricultural crops for pest control. Soil samples from farmer field at Memon Goth Karachi were collected randomly from a depth of 0-25cm. The persistence was determined at 100 ppm and 1000 ppm in soil as well as in combination with different fertilizers @ 1% viz: (Foliar fertilizer Polydol, DAP, SOP, and Urea) with tap water used for drinking purposes as well as hard water used for irrigation. The treated samples were kept under darkness to maintain the microbial activity and later analyzed through GC for persistence. The result of six months and one year study showed that no degradation occurred during the study period i.e. 100% recovery of the active ingredient was observed after one year under lab conditions. The microbial activity was also monitored by the standard dilution pour plate technique. The growth of Bacillus sp. was sensitive to chlorpyrifos treatment i.e. number of colony decreased whereas number of colonies of Klebsiellia sp. was found enhanced during the same treatment in the experiments.
Keywords: Chlorpyrifos; degradation; management; persistence; pesticide